Evaluation of plastic composites made with Laccosperma secundiflorum and Eremospatha macrocarpa canes - O. Adefisan, Olufemi; Wei, Liqing; G. McDonald, Armando (Maderas. Ciencia y Tecnología, 2017)
The feasibility of using rattan canes (Laccosperma secundiflorum and Eremospatha macrocarpa) as reinforced fillers for high density polyethylene based plastic composite production was investigated. Extruded composites were tested for water sorption, tensile and thermal properties. The results obtained indicated that the rattan composites were dimensionally (water absorption: 2,2-21,4% thickness swell: 0,9-5,3%) and thermally stable (Tc: 116,8-118,2°C) and possessed adequate tensile properties (7,3-21,7 MPa). Composites made from L. secundiflorum had higher strength and thermal properties but lower sorption values compared to those of E. macrocarpa. Differences in the densities of the composites and the anatomical structures of the rattans seemed to influence properties of the composites. PDF XML